2021
DOI: 10.1007/s10570-021-03807-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring digital image correlation technique for the analysis of the tensile properties of all-cellulose composites

Abstract: All-cellulose composites (ACCs) were prepared from filter paper via partial dissolution in the ionic liquid 1-ethyl-3-methylimidazolium acetate, and material tensile properties were investigated using various approaches. One is based on data directly taken from a tensile testing machine, and the other uses two-cameras stereovision with digital image correlation (DIC) technique. In the latter case, virtual extensometer with different locations on the sample and averaging over sample surface were tested. Nominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Therefore, the lm prepared by immersing ordinary paper in a cellulose solution has excellent optical properties, and its application value in optical equipment is also very considerable. It is worth noting that when the immersion time of the paper in the ionic liquid is different, the light transmittance and haze of the cellulose lm change (Chen et al 2021).…”
Section: Regenerated Cellulose Filmmentioning
confidence: 99%
“…Therefore, the lm prepared by immersing ordinary paper in a cellulose solution has excellent optical properties, and its application value in optical equipment is also very considerable. It is worth noting that when the immersion time of the paper in the ionic liquid is different, the light transmittance and haze of the cellulose lm change (Chen et al 2021).…”
Section: Regenerated Cellulose Filmmentioning
confidence: 99%
“…The structure of all cations and anions of ILs used in this study is outlined in Table . [Emim]­DEP, [Emim]­OAc, [Amim]­Cl, [DBNM]­DMP, and [DBNE]­DEP were synthesized and purified in our laboratory according to the well-established procedures described in the previous report. , The structure of ILs was determined by 1 H NMR (Bruker ARX-600, Brooke Co., Ltd, Germany) and FTIR (Rigaku, Japan), and the details are given in the Supporting Information of Figures S1–S8.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The discovery and rapid development of ionic liquids (ILs) reveals their unique solubility and H-bonding ability. Thereby, the application of ILs in dissolving cellulose have been extensively studied [10][11][12][13], in order to break the complex H-bond network of cellulose. Swatloski et al first reported that room-temperature ILs could be used for soluble, non-derived cellulose [14].…”
Section: Introductionmentioning
confidence: 99%